Lender of last resort policy: What reforms are necessary? - Ponce, Jorge (Journal of Financial Intermediation, 2010)
The Northern Rock bailout has raised concerns about the ability of current supervisory arrangements to deal with banking crises. This paper uses a formal model of a lender of last resort to derive policy implications regarding the optimal allocation of decision-making authority. Thereby, it contributes to the policy debate in the United Kingdom by proposing reforms to the current supervisory arrangements.